High-current pulse electron accelerators based on stepped forming lines - Gordeev, V.S.; Basmanov, V.F.; Myskov, G.A.; Filippov, V.O.; Nikol’ski, V.S.; Sulin, N.N.; Petrov, A.N.; Nazarenko, S.T.; Gridasov, A.P. (Вопросы атомной науки и техники, 2001)
There presented is a brief review of I-3000, STRAUS, STRAUS-2 and LIA-10M accelerators produced in VNIIEF over the period from 1981 to 1994. All the installations function in the mode of single pulses. Their distinction consists in using the systems of forming high-voltage pulses on the basis of stepped forming lines. Such installations formed of line sections of a similar electrical length with a stepped character of impedance variance provide a high efficiency and as a result of wave processes increase for a several time the output voltage as compared to the charge voltage of lines. The limiting energy of accelerated electrons for the created accelerators lies within the range from 2.3 to 25 MeV, beam current amplitude – from 20 to 50 kA, current pulse width at half-height – from 16 to 40 ns. The basic characteristics of each accelerator are presented.